The impact of election periods on public expenditure in the municipalities of Rio Grande do Sul, 2009 to 2016 - Lucion Puchale, Caroline (2019)
The objective of this study is to demonstrate the possible existence of opportunistic political-economic cycles in current and capital expenditures in the municipalities of the state of Rio Grande do Sul from 2009 to 2016. To this end, econometric analysis was used through the estimation of a panel data model. The results show that the electoral calendar only has an influence on the current expenditures of the municipalities in the evaluated period, since these are short-term expenses that are easily observed by the electorate. Therefore, this study contributes to the theory by showing that fluctuations in the economy, in terms of current expenditure, of the municipalities of Rio Grande do Sul for 2009 to 2016 are also explained by political variables, and not only by economic factors.